Analisis Prinsip Fisika pada Tiang Lumbung Padi sebagai Kearifan Lokal Masyarakat Toraja - Paulus Pulung; Enos Lolang; Gela M. Saka Bergita (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2023)
This research will provide knowledge about the existence of physics principles in rice barn poles. This study aims to analyze what physics principles just the one on the rice barn pole. The type of research used is qualitative research. Data collection was carried out through interviews, observation, and documentation. The research location was conducted in Lembang Roroan Barra'-Barra'. The results of the research show that there are physics principles to the rice barn poles that need to be known, such as density ( ), gravity (w), pressure (p), and balance (F). From data analysis density is strongly influenced by mass and volume. The higher the density of an object, the bigger it will be mass per volume. Stress can occur on the pillar with supporting stones Because the pressure generated on the pole is very large so that on the pole uses stone as a support. The balance can be seen in the pole assembly method which uses the pen and hole method as a static equilibrium